Dakwah Through Language and Local Wisdom as a Strategy for Spreading Islam Among the Dayak Tribe in Kalimantan - Mamun, Muhammad Yulian (Fakultas Dakwah UIN KHAS Jember, 2025)
This study is motivated by the challenges of Islamic proselytization (dakwah) among the Dayak communities in Kalimantan, who possess a distinct cultural identity and linguistic diversity. The use of the Indonesian language in dakwah is often perceived as “foreign” by 62% of rural populations, hindering both comprehension and acceptance of Islamic teachings. Consequently, there is a need for dakwah strategies that integrate local languages and cultural wisdom to foster closer connections with the community. This study aims to explore the role of local language and cultural approaches as effective strategies for spreading Islam among the Dayak people. A qualitative research method was employed, with fieldwork conducted in Central and West Kalimantan. Data were collected through in-depth interviews, participatory observation, and documentation. The findings reveal that: 1) The use of mother tongues enhances community understanding and engagement. Although dialect diversity presents challenges, this strategy proves more effective than neutral approaches such as using the Indonesian language in remote areas. 2) Local wisdom, including Dayak rituals such as Gawai and Tiwah, is adapted in dakwah to reinforce Islamic acceptance. Collaboration with traditional leaders broadens the reach of Islamic messages. However, ritual modifications must be approached carefully to avoid deviating from the core tenets of monotheism (tauhid). The Sarasehan Budaya serves as a notable example of integrating religious teachings with cultural expression.